2019
DOI: 10.1002/hep.30361
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Mediates the Susceptibility to Polymicrobial Sepsis‐Induced Liver Injury by Granisetron Generation in Mice

Abstract: Sepsis‐induced liver injury is recognized as a key problem in intensive care units. The gut microbiota has been touted as an important mediator of liver disease development; however, the precise roles of gut microbiota in regulating sepsis‐induced liver injury are unknown. Here, we aimed to investigate the role of the gut microbiota in sepsis‐induced liver injury and the underlying mechanism. Cecal ligation and puncture (CLP) was used to induce polymicrobial sepsis and related liver injury. Fecal microbiota tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 50 publications
1
108
0
Order By: Relevance
“…C57BL/6 mice were housed with a 12 hours’ light–dark cycle in specific pathogen-free facilities. FMT was performed according to a modified method described previously 16. Briefly, female mice aged 6–8 weeks were administered antibiotics (vancomycin, 100 mg/kg; neomycin sulfate, metronidazole and ampicillin, 200 mg/kg) intragastrically once daily for five consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice were housed with a 12 hours’ light–dark cycle in specific pathogen-free facilities. FMT was performed according to a modified method described previously 16. Briefly, female mice aged 6–8 weeks were administered antibiotics (vancomycin, 100 mg/kg; neomycin sulfate, metronidazole and ampicillin, 200 mg/kg) intragastrically once daily for five consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection [5][6][7] . The syndrome can be induced by a wide variety of microbes and, by definition, involves a maladaptive response to a pathogen 5 .…”
Section: The World Healthmentioning
confidence: 99%
“…The intestinal microbiota has been shown to play a central role in sensitization of sepsis-induced liver injury, and microbiota-associated granisetron production resulted in amelioration of liver injury during sepsis development in a mouse model of cecal ligation puncture. 77 A recent case series showcased beneficial outcomes with FMT-related reconstitution of the gut microbiome on immune checkpoint inhibitors in colitis associated with a relative increase in regulatory T-cells within the colonic mucosa. 78 Lu et al 79 showed that there was a higher relative abundance of Klebsiella, Escherichia and Shigella and reduced levels of beneficial butyrate-producing bacteria among liver transplant recipients.…”
Section: Gm In Liver Cancermentioning
confidence: 99%